Molecular characterisation of Shiga toxin-producing Escherichia coli O157:H7 isolates from cattle in eastern Turkey - Kalender, H.; Kilic, A. (Czech Academy Agricultural Sciences, 2016)
Shiga toxin-producing Escherichia coli (STEC) O157:H7 is an important foodborne pathogen worldwide. In Turkey, little is known about the molecular characteristics of STEC O157:H7 isolates. The aim of this study was to examine the genetic diversity of STEC O157:H7 isolates from cattle in Turkey using pulsed-field gel electrophoresis (PFGE). A total of 18 STEC O157:H7 strains were isolated from 540 rectal swab samples of slaughtered cattle in two abattoirs (coded A and B) located in eastern Turkey. The presence of virulence genes (stx1, stx2, hlyA and eae) was detected using the polymerase chain reaction. Of the 18 STEC O157:H7 isolates, 14 had stx2, hlyA, and eae genes. Four of the isolates were positive for stx1, stx2, hlyA, and eae genes. Thirteen different PFGE patterns were observed among the STEC O157:H7 isolates. The most common PFGE pattern was X1, which was detected in six STEC O157:H7 isolates. These six isolates contained the same virulence genes (stx2, eae and hlyA). However, some of the isolates containing the same virulence genes showed different PFGE profiles. Eleven different PFGE patterns were detected among the isolates from abattoir B, and two different PFGE patterns were detected among the isolates from abattoir A. The results of PFGE revealed a wide genetic diversity among the STEC O157:H7 isolates from cattle in Turkey. This is the first study on PFGE typing of STEC O157:H7 isolates from cattle in Turkey and further studies are needed.
Keywords: pulsed-field gel electrophoresis; virulence genes; bovine; rectal swabs; E. coli strains